Studying Islam in an age of disruption: towards knowledge integration - Widiyanto, Asfa (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2022)
This paper tries to offer an approach to studying Islam in the contemporary age by taking into account the socio-political contexts which surround the present-day Muslim communities. Islamophobia, post-truth, the era of identity, and post-orientalism pose new challenges to Islamic studies. The interdisciplinary approach is thus a necessity, in line with the complexity of the problems of contemporary Muslim societies. This study strives to investigate two main research problems, namely: (a) in which ways current socio-political circumstances pose challenges to the content and methodology of contemporary Islamic studies; (b) what kind of knowledge integration can be brought forward in response to these changing contexts. This paper argues that contemporary Islamic studies should move towards al-dirasa al-Islamiyya al-muwassa’a (Islamic studies in its widest sense) by integrating Islamic and modern scholarship. This knowledge integration is strategic in producing knowledge that is both up-to-date and deep-rooted in society. It should also involve the integration of perspectives and worldviews so that it may lead to the production of balanced knowledge, in the sense of not being trapped in apologetics and excessive criticism. This knowledge integration will be more embedded in society if it is developed into a knowledge culture.